Preparation method of antioxidant TiVCTx, adsorbent and application of adsorbent in adsorption of methylene blue
By adding antioxidants to the TiVCTX solution to form chelation, MXene's low antioxidant and insufficient adsorption performance in adsorption of methylene blue was solved, and its antioxidant and adsorption performance was significantly improved.
Patent Information
- Application Number
- CN202510209101.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-18
AI Technical Summary
The existing MXene has low oxidation resistance and insufficient adsorption performance in adsorption of methylene blue, especially in water, which leads to damage to the nanosheet structure and reduced adsorption capacity.
By adding oxalic acid, sodium citrate or tartaric acid to the TiVCTX solution as an antioxidant, chelating is formed, and the antioxidant and adsorption properties of TiVCTX are enhanced.
It significantly improves TiVCTX's antioxidant and ability to adsorb methylene blue, extends its stability in the aqueous environment, and enhances its binding ability to methylene blue.
Smart Images

Figure CN119838571A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adsorption materials, and in particular to an anti-oxidation TiVCT X Preparation method, adsorbent and application of adsorbing methylene blue. Background Art
[0002] MXenes are an emerging type of two-dimensional layered nanomaterials that are considered to be excellent adsorbent materials due to their hydrophilicity, large specific surface area, high layer spacing, and abundant surface functional groups.
[0003] As an important part of the global industry, the dye industry plays a pivotal role in the fields of textiles, leather, printing and dyeing, plastics and paints. Methylene blue (MB), as a cationic dye, has been widely used in these industrial applications due to its excellent chromaticity and stability. However, the large-scale discharge of methylene blue will seriously pollute water bodies, causing turbidity in water bodies, affecting water quality, and then hindering the propagation of light, inhibiting the photosynthesis of aquatic organisms, and thus destroying the balance of aquatic ecosystems. More seriously, methylene blue is not only toxic and can interfere with the physiological activities of organisms, causing biological poisoning, suffocation and even death, but also its potential carcinogenicity and mutagenicity pose a threat to human health. Long-term exposure to water contaminated by methylene blue may cause skin allergies, respiratory problems, and increase the risk of cancer. In view of the dual threat of methylene blue to aquatic ecosystems and human health, it is particularly important to effectively treat industrial wastewater containing methylene blue dyes. At present, a number of technologies have been applied to dye wastewater treatment, including photocatalysis, ion exchange, microbial degradation, advanced oxidation industry and adsorption. Among them, the adsorption method is recognized as an efficient and sustainable removal method for methylene blue due to its significant advantages such as simple operation, high cost-effectiveness, high treatment efficiency and environmental friendliness.
[0004] At present, although there are precedents of using MXene to adsorb methylene blue at home and abroad, M3X2T is usually used. X Ti3C2T X However, MXene still has some shortcomings in the adsorption of methylene blue: on the one hand, its ability to adsorb methylene blue needs to be improved, and on the other hand, MXene oxidizes and degrades faster in water than in organic solvents, air or polymer matrices. Water molecules play a key role in the degradation of MXene, which destroys its original special nanosheet structure and loses its unique properties, further weakening MXene's ability to adsorb methylene blue. Therefore, there is an urgent need for effective strategies to improve the adsorption performance while improving the oxidation resistance of MXene. Summary of the invention
[0005] The problem to be solved by the present invention is to provide an antioxidant TiVCT X The invention discloses a preparation method, an adsorbent and application thereof for adsorbing methylene blue to overcome the defects of the existing MXene, such as low oxidation resistance and low adsorption performance of methylene blue.
[0006] The technical solution adopted by the present invention to solve the technical problem is: an antioxidant TiVCT X The preparation method comprises the following steps:
[0007] S1. Preparation of TiVCT X Solution;
[0008] S2, to the TiVCT X Antioxidants are added to the solution, and after mixed reaction, the carboxyl groups in the antioxidant molecules can react with TiVCT X The Ti and / or V in the solution form a chelate reaction, thereby allowing the antioxidant molecules to bind to the TiVCT X Closely integrated with TiVCT X A protective layer is formed on the surface, thus obtaining anti-oxidation TiVCT X Solution;
[0009] Wherein, the antioxidant is oxalic acid, sodium citrate or tartaric acid.
[0010] As a further improvement of the present invention, in S1, the TiVCT X The solution is prepared by a mixed etching method of LiF and HCl solution.
[0011] As a further improvement of the present invention, the preparation of TiVCT X The specific operation steps of the solution are as follows:
[0012] First, TiVAlC and LiF were mixed into HCl solution in proportion, deionized water was added after stirring, and the solution was repeatedly centrifuged and washed until the pH value of the solution was adjusted to 7; then, the solution was placed in a cold bath for ultrasonic treatment, and then the solution was centrifuged and the supernatant was collected to finally obtain TiVCT. X Solution.
[0013] As a further improvement of the present invention, when the antioxidant is oxalic acid, the oxalic acid and the TiVCT X The mass ratio is (1~20):4.
[0014] As a further improvement of the present invention, when the antioxidant is sodium citrate, the sodium citrate and the TiVCT X The mass ratio is (1~20):4.
[0015] As a further improvement of the present invention, when the antioxidant is tartaric acid, the tartaric acid and the TiVCT X The mass ratio is (1~5):1.
[0016] The present invention also provides an adsorbent, the adsorbent is composed of the above-mentioned antioxidant TiVCT X It is prepared by the preparation method.
[0017] The present invention prepares an adsorbent for adsorbing methylene blue, and the adsorbent relies on TiVCT X While adsorbing methylene blue, the carboxyl groups in the antioxidant molecules can undergo Bloch reaction with the amino groups in the methylene blue, thereby significantly improving the adsorption performance of the adsorbent for methylene blue.
[0018] The beneficial effects of the present invention are as follows: the present invention provides an antioxidant TiVCT X Preparation method, adsorbent and application of methylene blue adsorption by using three antioxidants, OA, SC and TA, to X After antioxidant treatment, OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X , in TiVCT X The synergistic effect between the bimetallic crystal structure Ti and / or V makes the MXene active sites fully exposed, further enhancing its adsorption performance. X The chelation of the atoms at the edge of the nanosheets forms a dense protective layer, which reduces the effect of OH- on TiVCT in water. X The damage of TiVCT has significantly improved its oxidation resistance. X The excellent adsorption capacity of the antioxidant itself is fully released; further, the adsorbent prepared by the preparation method can be used to adsorb methylene blue. While the adsorbent relies on TiVCTX to adsorb methylene blue, the carboxyl group in the antioxidant molecule can undergo a Bloch reaction with the amino group in the methylene blue, further enhancing the binding ability with methylene blue, and ultimately making the adsorbent show excellent adsorption performance for methylene blue. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The antioxidant TiVCT of the present invention X A flowchart of the steps of the preparation method;
[0020] Figure 2 The oxalic acid, sodium citrate and tartaric acid in the present invention are respectively X Diagram of the molecular structure that forms the chelation effect;
[0021] Figure 3 For the present invention, oxalic acid / sodium citrate / tartaric acid is added to TiVCT X Schematic diagram of the solution undergoing antioxidant treatment;
[0022] Figure 4 TiVCT of the present invention X Schematic diagram of nanosheet preparation;
[0023] Figure 5 (a) is TiVAlC, TiVCT X OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X X-ray diffraction pattern immediately after successful preparation; (b) TiVCT X OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X X-ray diffraction pattern after 14 days of storage;
[0024] Figure 6 TiVAlC, TiVCT X OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X Fourier transform infrared spectrum of
[0025] Figure 7 (a), (b), (c), and (d) are TiVCT X OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X Scanning electron microscope images taken immediately after successful preparation; (e), (f), (g), and (h) are TiVCT X OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X Scanning electron microscopy images taken after 14 days of placement;
[0026] Figure 8 The TiVCT without antioxidant treatment and the TiVCT with antioxidant treatment of the present invention X Optical photographs of color changes during storage for 0-14 days;
[0027] Fig. 9 (c) is TiVCT XSchematic diagram of the antioxidants bound to the surface of TiVCTx by chelation reaction without and with antioxidant treatment to enhance the adsorption capacity of methylene blue through Bloch reaction; (d) is a schematic diagram of the binding of oxalic acid, sodium citrate, and tartaric acid to methylene blue through Bloch reaction;
[0028] Fig.10 (a), (b), and (c) are the effects of different amounts of oxalic acid, sodium citrate, and tartaric acid on TiVCT. X Bar graph of the effect of adsorption of methylene blue performance;
[0029] Fig.11 (a), (b), and (c) are the effects of different pH values on OA-TiVCT. X ,SC-TiVCT X and TA-TiVCT X Bar graph of the effects of adsorption performance;
[0030] Fig.12 (a), (b), and (c) are OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X Bar graph showing the effect of different initial concentrations on the adsorption performance of methylene blue;
[0031] Fig.13 (a), (b), (c), and (d) are TiVCT X OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X Line graph of the effect of storage for 0 and 14 days on zeta potential in the pH range 3-11. DETAILED DESCRIPTION
[0032] The technical solutions provided by various embodiments of the present application are described below in conjunction with the accompanying drawings.
[0033] See also Figure 1 The present invention provides an antioxidant TiVCT X The preparation method comprises the following steps:
[0034] S1. Preparation of TiVCT X Solution;
[0035] S2, TiVCT X Antioxidants are added to the solution, and after mixed reaction, the carboxyl groups in the antioxidant molecules can react with TiVCT X The Ti and / or V in the solution form a chelate reaction, thereby allowing the antioxidant molecules to bind to the TiVCT XClosely integrated with TiVCT X A protective layer is formed on the surface, thus obtaining anti-oxidation TiVCT X Solution.
[0036] Among them, the antioxidants used are oxalic acid (OA), sodium citrate (SC) or tartaric acid (TA). These antioxidant molecules all contain multiple carboxyl groups, of which OA molecules contain two carboxyl groups, SC molecules contain three carboxyl groups and one hydroxyl group, and TA molecules contain two carboxyl groups and two hydroxyl groups. These carboxyl groups can react with TiVCT X Ti or V in Figure 2 The chelation reaction is formed in the manner shown, so that the antioxidant molecules are bound to TiVCT X Tightly bound, resulting in antioxidants in TiVCT X A protective layer is formed on the surface (such as Figure 3 As shown), effectively resisting OH in water - The erosion of TiVCT X Able to maintain long-term stability in water environment at room temperature.
[0037] In S1, TiVCT X The solution was prepared by a mixed etching method of LiF and HCl solution. Preparation of TiVCT X The specific operation steps of the solution are as follows:
[0038] like Figure 4 As shown, first, 1g TiVAlC (>98wt%, 200 mesh), 1.6g lithium fluoride (LiF) and 20ml hydrochloric acid (HCl) solution were mixed and stirred for etching at 500rpm and 45°C for 48 hours. Subsequently, deionized water was added and centrifuged at 5000rpm for 5 minutes, and the supernatant was discarded. This washing process was repeated until the pH value of the solution was adjusted to 7. Next, the solution was placed in a cold bath for 2.5 hours of ultrasonic treatment, and then centrifuged at 3500rpm for 30 minutes. The collected supernatant was TiVCT. X Solution.
[0039] Compared with traditional MXene such as Ti3C2T X In comparison, the bimetallic MXene used in the present invention, namely TiVCT X Due to its unique crystal structure, it leads to a special synergistic effect between Ti and / or V, which enhances the interfacial chemical bonding ability and is conducive to the full exposure of active sites, which means that it has a more superior adsorption potential and can perform outstandingly in the adsorption of methylene blue.
[0040] It should be noted that the raw materials TiVAlC, lithium fluoride, hydrochloric acid, methylene blue, oxalic acid, sodium citrate and tartaric acid in the present invention can be directly purchased on the market.
[0041] In S2, when oxalic acid is used as the antioxidant, the oxalic acid and TiVCT X The mass ratio of is (1-20):4, preferably 1:1. When the antioxidant is sodium citrate, sodium citrate and TiVCT X The mass ratio of tartaric acid to TiVCT is (1-20):4, preferably 1:1. When tartaric acid is used as the antioxidant, the tartaric acid and TiVCT X The mass ratio is (1-5):1, preferably 4:1.
[0042] The specific operation steps of S2 are as follows:
[0043] Accurately weigh a certain amount of OA, SC and TA according to the corresponding proportions and add them to the TiVCT X The mixed solution was then placed in a centrifuge tube and hand-shaken for 10 minutes to obtain the antioxidant TiVCT X The solutions were recorded as OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X .
[0044] The following is an analysis of OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X And the comparative example is TiVCT without antioxidant treatment X to illustrate their respective antioxidant properties.
[0045] TiVCT X OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X The pH values of the four solutions were adjusted to about 6, and the concentration was diluted to 2 mg / mL. 10 mL of each solution was vacuum filtered to form a film to prepare samples. The crystal structure of the samples was analyzed by X-ray diffractometer with a test angle of 5-90° and a scanning speed of 2° / min.
[0046] Precursor TiVAlC and TiVCT X OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X The XRD pattern on day 0, i.e. immediately after the preparation, is as follows: Figure 5(a) From TiVAlC to TiVCT X The transformation is characterized by the almost complete disappearance of the (103) and (100) peaks, indicating that the etching process successfully removed the Al atomic layer. In addition, the (002) peak shifted to a lower angle, from 13.31° to 6.71°, indicating that the etching process effectively increased the interlayer spacing of the precursor and successfully prepared TiVCT. X .
[0047] Figure 5 (b) shows TiVCT X OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X XRD patterns after 14 days in solution. It can be observed that all four samples show severe and similar impurity peaks in the 20°-30° range, which is a clear sign of oxidation. By comparing the (002) main peak, it can be seen that TiVCT X and OA-TiVCT X The main peaks of SC-TiVCT have almost disappeared, indicating that their structures have been almost completely degraded and are the most oxidative. X The main peak intensity of TA-TiVCT is slightly stronger than the first two, indicating that SC effectively enhances the antioxidant properties of TiVCTx. X The (002) main peak intensity has the most significant advantage, indicating that TA-TiVCT X The structure is kept the best and is TiVCT X Provides maximum antioxidant performance enhancement.
[0048] Figure 6 TiVCT X And the treated samples OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X Fourier transform infrared (FTIR) spectra. Through comparative analysis, it was found that the surface functional groups of the samples increased significantly after antioxidant treatment. Specifically, 525cm -1 The absorption peak at 1316 cm is attributed to the in-plane rocking vibration of COO-, while the absorption peak at 1316 cm -1 and 1415cm -1 The absorption peak is the in-plane bending vibration of COO-. -1 The absorption peak at 775cm -1 The absorption peak at 965 cm-1 corresponds to the in-plane rocking vibration of CH, the absorption peak at 3438 cm-1 corresponds to the out-of-plane bending vibration of C-OH, and the absorption peak at 1447 cm-1 corresponds to the out-of-plane bending vibration of C-OH. -1The absorption peak of the hydroxyl group corresponds to the vibration of the hydroxyl group. These results show that the TiVCT treated with antioxidant X The samples were bound to the antioxidants by chelation, which introduced carboxyl and hydroxyl functional groups.
[0049] Furthermore, TiVCT X OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X The morphological characteristics of the cells were characterized by scanning electron microscopy at day 0 and day 14. Figure 7 (a) is the precursor TiVAlC and the TiVCT obtained after etching. X The precursor TiVAlC exhibits a densely packed block structure with a size of approximately 16 microns in length and 12 microns in width. After etching, an ultra-thin, flat TiVCT X Nanosheets. These TiVCT X The dimensions of the nanosheets are approximately 8 micrometers long and 5 micrometers wide, which are typical features of a 2D layered material structure.
[0050] Figure 7 (b)-(d) show that after adding antioxidants for antioxidant treatment, TiVCT X The morphology did not change significantly, and all appeared as ultra-thin and smooth few-layer nanosheets. However, after standing in the solution for 14 days, the morphology of different materials changed significantly. Figure 7 TiVCT shown in (e) X After 14 days of standing, the nanosheets were severely wrinkled, and their original ultra-thin two-dimensional nanosheet morphology was completely lost. This was obviously caused by the severe oxidation of the material. X (like Figure 7 (f)) maintains the basic structure of the ultrathin nanosheet. Figure 7 In (g) and (h), SC-TiVCT X and TA-TiVCT X After 14 days of standing, no wrinkles appeared. The ultrathin two-dimensional nanosheet structures of the two materials remained intact, and the surface was smooth and free of impurities, showing excellent stability. These observations further confirm the role of antioxidants in improving TiVCT X Important role in material stability.
[0051] Next, OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X The antioxidant properties were further described.
[0052] TiVCT X Whether it is oxidized can be directly reflected from the dispersion state of the solution, so the TiVCT without and with antioxidants is X The storage time of the solution is tested. The actual picture of the solution with a storage time of 0-14 days is as follows Figure 8 As shown. Figure 8 In the experiments shown, TiVCT at a concentration of 2 mg / mL and a pH of 6 was added. X OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X The solutions are stored in glass bottles and deaeration is avoided during the entire storage process so that these solutions can fully contact with the air in the top of the bottle. X On the fourth day of standing, the solution was stratified. The upper solution turned brown and a precipitate appeared in the lower layer. The precipitate continued to decompose over time, resulting in a decrease in the thickness of the precipitate. This is the result of TiVCT. X Significant signs of severe oxidation. TA-TiVCT X On the third day, stratification occurred, but there was no precipitation or color change. OA-TiVCT X On the sixth day of standing, stratification occurred, but it was different from TiVCT X Different, OA-TiVCT X The upper layer is a colorless transparent liquid, and the lower layer is a black precipitate, and the black precipitate has basically not decomposed. X The solution remained in a normal solution dispersion state throughout the experiment, which fully proved that the SC-TiVCT X It has the best colloidal solution stability among all the tested samples. The results show that TiVCT with added antioxidant ingredients X The key to showing better dispersibility is that these antioxidants can effectively prevent TiVCT X Of the three antioxidants tested, SC-TiVCT X The dispersion effect of X , while TA-TiVCT X The effect is relatively weak.
[0053] The present invention also provides an adsorbent, the adsorbent is composed of the above-mentioned antioxidant TiVCT X The preparation method is prepared.
[0054] See also Fig. 9(a) and (b), the adsorbent of the present invention is used to adsorb methylene blue (MB), and the adsorbent relies on TiVCT X While adsorbing methylene blue, the carboxyl group in the antioxidant molecule can undergo Bloch reaction with the amino group in methylene blue, significantly improving the adsorption performance of the adsorbent for methylene blue.
[0055] Among them, the chemical formulas of Bloch reactions of OA, SC and TA with MB are as follows:
[0056] HOOC-COOH+HN(C6H4NH2)2Cl——→
[0057] HOOC-CO-NH-(C6H4NH2)2Cl+H2O
[0058] HOOC-CH2-CH2-COOH+HN(C6H4NH2)2Cl——→
[0059] HOOC-CH2-CH2-CO-NH-(C6H4NH2)2Cl+H2O
[0060] HOOC-CHOH-CHOH-COOH+HN(C6H4NH2)2Cl——→
[0061] HOOC-CHOH-CHOH-CO-NH-(C6H4NH2)2Cl+H2O
[0062] In order to further explore the effects of the dosage of three antioxidants, OA, SC and TA, on TiVCT X In order to investigate the specific effects of the adsorption performance of MB, the present invention conducted a series of experiments.
[0063] Under the premise of maintaining the same other conditions, by adding 20mg TiVCT X 5mlTiVCT X Different masses of OA (0 mg, 5 mg, 10 mg, 20 mg, 40 mg, 100 mg), SC (0 mg, 5 mg, 10 mg, 20 mg, 40 mg, 100 mg) and TA (0 mg, 20 mg, 40 mg, 60 mg, 80 mg, 100 mg) were added to the solution. Under the same experimental conditions of pH = 9, the MB solution with an initial concentration of 350 mg / L was adsorbed.
[0064] from Fig.10 (a), (b) and (c) show that after adding three antioxidants for antioxidant treatment, TiVCT X However, with the increase of OA, SC, and TA dosage, TiVCT XThe adsorption amount of MB showed a trend of first increasing and then decreasing. When the addition amount of OA and SC was 20 mg, the removal effect of MB was the best, and the maximum adsorption amount was 1705.5 mg / g and 1718.07 mg / g respectively. X The best ratio is 1:1 with SC and OA. When the mass of TA is 80 mg, the adsorption effect is the best, and the adsorption amount is 1738.3 mg / g, that is, TiVCT X The optimal ratio of TA is 1:4. This is attributed to the fact that when the amount of antioxidant is small, the TiVCT after antioxidant treatment X The improvement of antioxidant activity is limited; with a moderate increase in the amount of antioxidant, TiVCT X The antioxidant property of TiVCT is further improved, thereby reducing the degree of oxidation during the adsorption process and increasing the adsorption amount. However, when the amount of antioxidant added exceeds a certain threshold, TiVCT X The antioxidant activity of MB gradually reaches saturation. If the dosage of antioxidant continues to increase, more impurity ions will be introduced, resulting in competition between impurity ions and MB during the adsorption process, resulting in a negative effect of decreased adsorption.
[0065] In order to avoid the interference of antioxidant adsorption of MB on the analysis of experimental results, control experiments were conducted on the adsorption of MB by three antioxidants separately. In the MB solution with an initial concentration of 500 mg / g, after the three antioxidants were added for adsorption for one hour, there was no obvious change in the MB concentration, indicating that the antioxidant alone had basically no adsorption effect on MB.
[0066] Fig.11 (a), (b), and (c) are the effects of different pH values on OA-TiVCT. X ,SC-TiVCT X and TA-TiVCT X Bar graph showing the effect of adsorption on the adsorption performance. MB-initial =500mg / L, TiVCT X TiVCT of 20 mg of TiVCT treated with three antioxidants under the same experimental conditions X The adsorption performance of MB generally increases with the increase of pH value. When the pH value reaches 11, OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X The adsorption performance of the antioxidants all reached the peak, and the adsorption amounts were 1748.71 mg / g, 1772.13 mg / g, and 1770.2 mg / g, respectively. XThe dense and efficient protection provided by the anti-oxidation treatment makes TiVCT X It can remain relatively stable in an environmental solution with a pH value of 11.
[0067] Fig.12 (a), (b), and (c) show OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X Effect of initial MB concentration on adsorption performance at pH 11. MB-initial =1200-1900mg / L, TiVCT X The mass is 20 mg. OA-TiVCT X The adsorption amount of SC-TiVCT is slightly lower than that of SC-TiVCT X and TA-TiVCT X When the initial MB concentration reached 1500 mg / L, the adsorption reached a maximum value of 6750.81 mg / g and no longer increased. X The adsorption performance is second only to TA-TiVCT X When the initial MB concentration reached 1900 mg / L, the adsorption capacity was 8006.96 mg / g. X The adsorption performance is the best. When the initial MB concentration reaches 1900 mg / L, the adsorption amount is 8061.03 mg / g. X ,SC-TiVCT X and TA-TiVCT X The maximum adsorption capacity of the products has been dramatically improved, far exceeding the adsorption capacity values in the existing technologies, which undoubtedly demonstrates their significant advantages and leading position in adsorption performance.
[0068] like Fig.13 (a), (b), (c), and (d) are TiVCT X OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X Zeta potential measurement results on the 0th and 14th days of static standing. On the 0th day of static standing, TiVCT can be observed. X However, compared with untreated TiVCT X Compared with TiVCT with added antioxidants X The overall electronegativity of the solution is enhanced. Comparison of their Zeta potential at their respective optimal adsorption pH, i.e., TiVCT XpH = 9 and OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X It can be concluded that the Zeta potential of the latter three is more negative, the electrostatic attraction to MB cation is stronger, and it is more conducive to the occurrence of electrostatic adsorption. It also shows that OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X The adsorption of MB involves electrostatic adsorption. This phenomenon is attributed to the interaction between the acid ions in the antioxidant and TiVCT. X Specifically, these acid ions are negatively charged and react with TiVCT X After the Ti and V atoms in the chelate, they tightly surround the TiVCT X A protective barrier forms around the nanosheets.
[0069] The above experimental results show that TiVCT treated with SC and TA X (i.e. SC-TiVCT X and TA-TiVCT X ) is superior to OA-treated TiVCT in terms of antioxidant properties and MB adsorption performance. X (i.e. OA-TiVCT X ). This indicates that SC and TA have X The chelation between SC and TA molecules is stronger and can anchor MB cations more effectively. This is because the hydroxyl groups in SC and TA molecules promote the interaction with TiVCT. X The chelation effect of antioxidant molecules and TiVCT enhances its antioxidant and adsorption properties. X The chelation effect of MB and the Bloch reaction with MB work together to improve the overall performance of the adsorbent. X The excellent adsorption capacity of MXene itself for MB and the synergistic effect of the two make the adsorption performance of MXene-based materials as adsorbents increased exponentially.
[0070] In summary, the present invention uses OA, SC, and TA as three antioxidants to treat TiVCT X After antioxidant treatment, OA-TiVCT X ,SC-TiVCT X and TA-TiVCT X , in TiVCT XThe synergistic effect between the bimetallic crystal structure Ti and / or V makes the MXene active sites fully exposed, further enhancing its adsorption performance. X The chelation of the atoms at the edge of the nanosheets forms a dense protective layer, which reduces the effect of OH- on TiVCT in water. X The damage of TiVCT has significantly improved its oxidation resistance. X The excellent adsorption capacity of the material is fully released; coupled with the Bloch reaction between the antioxidant molecules and MB, the binding capacity with MB is further enhanced, and finally the adsorbent bursts out such excellent adsorption performance. The present invention not only successfully prepares TiVCT with long-term stability X Materials, and also deeply explored its potential in the field of adsorption, promoted the research and application of MXene materials and provided new perspectives and directions.
[0071] The same and similar parts between the various embodiments in this specification can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0072] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. An antioxidant TiVCT X The preparation method is characterized in that The following steps are involved: S1. Preparation of TiVCT X Solution; S2, to the TiVCT X Antioxidants are added to the solution, and after mixed reaction, the carboxyl groups in the antioxidant molecules can react with TiVCT X The Ti and / or V in the solution form a chelate reaction, thereby allowing the antioxidant molecules to bind to the TiVCT X Closely integrated with TiVCT X A protective layer is formed on the surface, thus obtaining anti-oxidation TiVCT X Solution; Wherein, the antioxidant is oxalic acid, sodium citrate or tartaric acid.
2. The antioxidant TiVCT according to claim 1 X The preparation method is characterized in that: In S1, the TiVCT X The solution is prepared by a mixed etching method of LiF and HCl solution.
3. The antioxidant TiVCT according to claim 2 X The preparation method is characterized in that Preparation of TiVCT X The specific operation steps of the solution are as follows: First, TiVAlC and LiF were mixed into HCl solution in proportion, deionized water was added after stirring, and the solution was repeatedly centrifuged and washed until the pH value of the solution was adjusted to 7; then, the solution was placed in a cold bath for ultrasonic treatment, and then the solution was centrifuged and the supernatant was collected to finally obtain TiVCT. X Solution.
4. The antioxidant TiVCT according to claim 1 X The preparation method is characterized in that: When the antioxidant is oxalic acid, the oxalic acid and the TiVCT X The mass ratio is (1~20):
4.
5. The antioxidant TiVCT according to claim 1 X The preparation method is characterized in that: When the antioxidant is sodium citrate, the sodium citrate and the TiVCT X The mass ratio is (1~20):
4.
6. The antioxidant TiVCT according to claim 1 X The preparation method is characterized in that: When the antioxidant is tartaric acid, the tartaric acid and the TiVCT X The mass ratio is (1~5):
1.
7. An adsorbent, characterized in that: The adsorbent is the antioxidant TiVCT according to any one of claims 1 to 6 X The preparation method is prepared.
8. Use of the adsorbent according to claim 7 in adsorbing methylene blue, wherein the adsorbent relies on TiVCT X While adsorbing methylene blue, the carboxyl groups in the antioxidant molecules can undergo Bloch reaction with the amino groups in the methylene blue, thereby significantly improving the adsorption performance of the adsorbent on methylene blue.